D‐2‐hydroxyglutaric aciduria Type I: Functional analysis of D2HGDH missense variants. Issue 7 (13th April 2019) - Pop, Ana; Struys, Eduard A.; Jansen, Erwin E. W.; Fernandez, Matilde R.; Kanhai, Warsha A.; van Dooren, Silvy J. M.; Ozturk, Senay; van Oostendorp, Justin; Lennertz, Pascal; Kranendijk, Martijn; van der Knaap, Marjo S.; Gibson, K. Michael; et al.
Abstract: D‐2‐hydroxyglutaric aciduria Type I (D‐2‐HGA Type I), a neurometabolic disorder with a broad clinical spectrum, is caused by recessive variants in the D2HGDH gene encoding D‐2‐hydroxyglutarate dehydrogenase (D‐2‐HGDH). We and others detected 42 potentially pathogenic variants in D2HGDH of which 31 were missense . We developed functional studies to investigate the effect of missense variants on D‐2‐HGDH catalytic activity. Site‐directed mutagenesis was used to introduce 31 missense variants in the pCMV5‐ D2HGDH expression vector. The wild type and missense variants were overexpressed in HEK293 cells. D‐2‐HGDH enzyme activity was evaluated based on the conversion of [ 2 H4 ]D‐2‐HG to [ 2 H4 ]2‐ketoglutarate, which was subsequently converted into [ 2 H4 ]L‐glutamate and the latter quantified by LC‐MS/MS. Eighteen variants resulted in almost complete ablation of D‐2‐HGDH activity and thus, should be considered pathogenic. The remaining 13 variants manifested residual activities ranging between 17% and 94% of control enzymatic activity. Our functional assay evaluating the effect of novel D2HGDH variants will be beneficial for the classification of missense variants and determination of pathogenicity.